2017
DOI: 10.1017/s0033291717001106
|View full text |Cite
|
Sign up to set email alerts
|

Ten month outcome of cognitive behavioural therapy v. interpersonal psychotherapy in patients with major depression: a randomised trial of acute and maintenance psychotherapy

Abstract: CBT and IPT are effective treatments for major depression over the longer term. CBT may work more quickly. Personality variables are the most relevant predictors of outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…In previous randomized trials comparing CT and IPT head-to-head, various predictors and moderators of posttreatment outcome were identified (Sotsky et al, 1991;Joyce et al, 2007;Luty et al, 2007;Ryder et al, 2010;Carter et al, 2011;Mulder et al, 2017). Only one study by Mulder et al (2017) also identified predictors and moderators of longterm outcomes during maintenance CT and IPT following acute phase treatment. The findings of this study were not in line with our results: no significant moderators were identified, and personality variables were identified as significant predictors.…”
Section: Predictors and Moderatorsmentioning
confidence: 99%
“…In previous randomized trials comparing CT and IPT head-to-head, various predictors and moderators of posttreatment outcome were identified (Sotsky et al, 1991;Joyce et al, 2007;Luty et al, 2007;Ryder et al, 2010;Carter et al, 2011;Mulder et al, 2017). Only one study by Mulder et al (2017) also identified predictors and moderators of longterm outcomes during maintenance CT and IPT following acute phase treatment. The findings of this study were not in line with our results: no significant moderators were identified, and personality variables were identified as significant predictors.…”
Section: Predictors and Moderatorsmentioning
confidence: 99%
“…Two studies were drug trials, while the other two were psychotherapy studies. Details of each study are reported elsewhere (Carter et al, 2013;Joyce et al, 1994Joyce et al, , 2002Mulder et al, 2017).…”
Section: Samplementioning
confidence: 99%
“…Exclusion criteria were a diagnosis of schizophrenia, mania, severe substance use disorder (mild to moderate was acceptable) and significant physical illness. Two trials also excluded those who had not benefitted from psychotherapy over the prior year (Carter et al, 2013;Mulder et al, 2017). Participants were all recruited from the same geographic area, Canterbury, New Zealand, and were similar with regard to demographic and diagnostic variables.…”
Section: Samplementioning
confidence: 99%
“… 3 , 4 To date, several alternative treatments are available, such as electroconvulsive therapy (ECT) and nonpharmacological treatments like cognitive behavior therapy or interpersonal psychotherapy. 5 ECT is used to induce neuromodulation, 6 which is highly effective in TRD with 60%–80% of patients achieving remission. 7 , 8 Interestingly, combination of ECT with aerobic exercise training ameliorates the remission rates of patients with MDD when compared with ECT alone.…”
Section: Introductionmentioning
confidence: 99%